Conversational Implicature in the Qur’anic text – A deliberative study of the verses of family discourse – - Zataar, Zein Baker (Journal of Humanities & Social Sciences, 2021)
This research aims to examine the verses of family discourse in the Qur’anic text in a deliberative manner in accordance with the conversational implicature theory, which considers that any dialogue between two parties includes an explicit meaning, and an implicit meaning that is understood from the context. The concept of conversational implicature was explained in this study. In addition, the study investigated the conversational implicature included in the verses of family discourse among family members and among the spouses themselves. The research concluded that the rhetorical methods contained in the family discourse verses in the Qur’anic text carry implicit meanings that are understood within the context in which they are mentioned.